The Christian nursing profession - Martini, Carlo Maria (Medicina e Morale, 1990)
The nursing world is at the center of various problems. Starting from the concrete situations of our time, the author deals with the theme of nursing professionalism from the ethical and Christian point of view. The profound ideals which are inherent in nursing have to be emphasized. The nursing world has to become more aware of the crucial role it plays, so the need for up-to-date training has become more and more important. Moreover, a real collaboration between voluntary helpers and nurses encorages the nurse to experience values like altruism more intensely.